Milk production, composition, and udder morphometric traits across various lactation stages of Boer goats and their crosses in Ethiopia - Bekele, Rekik; Abebe, Girma; Banerjee, Sandip (Frontiers in Animal Science, 2025)
This study was conducted at the Sheep and Goat Crossbreeding and Multiplication Center of Hawassa University, Ethiopia, to evaluate milk production, composition, and udder morphology in Boer goats and their crosses. The relationships between these traits and their predictive potential for milk yield across lactation stage were analyzed. The study involved fourteen multiparous goats (seven Boer and seven crossbred) which were monitored over a 14-week of lactation period. Milk yield was measured weekly using the weigh-suckle-weigh method, while milk composition was determined biweekly using a standard laboratory procedure, and udder morphometric traits were measured biweekly using a measuring tape and an angle ruler. Data were analyzed using SPSS software (version 20), applied repeated generalized linear models (GLM), Pearson correlations, and stepwise regression. Results showed that Boer goats produced significantly higher milk yields (1.22 ± 0.05 kg/day) compared to crossbred goats (1.01 ± 0.04 kg/day), with both breeds reaching peak production in the third week of lactation. Boer goats also exhibited milk with higher total solids (15.19%), fat (4.64%), protein (4.06%), and solid not fat (10.61%) contents (p < 0.05). A significant negative correlation (r = -0.42) was observed between milk yield and fat percentage. Boer goats exhibited better udder morphometric traits compared to crossbred goats. A strong and positive association between udder and teat circumference and milk yield was noted throughout the lactation period. Regression analysis identified these traits as the strongest predictors of milk yield, explaining 72.8% of the variation in Boer goats and 69.1% in crossbred goats. The findings of this study contribute to ongoing breed characterization efforts in the country and also highlight the possibility of using udder morphometric traits to estimate milk production, replacing the weigh-suckle-weigh method, which is cumbersome and difficult to apply to a larger population.